The Influence of Working Capital and Organization on the Financial Performance of Small-Sized Enterprises in Jayapura City - Mugiati, Mugiati (Journal of Economics and Behavioral Studies, 2015)
This study aims to identify and analyze the influence of working capital and organization, on the financial performance of Small-sized enterprise in Jayapura City. Data collection methods used were observation, interviews, and questionnaires. Data were analyzed by applying SEM (structural equation modeling analysis method by making use of Amos Software. The results showed that the factors of working capital factor affect the financial performance of small-sized enterprise in Jayapura. Then the organization factor does not affect the financial performance of small-sized enterprise in Jayapura.